2020
DOI: 10.1155/2020/9601901
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Sorghum (Sorghum bicolor L. Moench) Genotypes for Pre- and Post-attachment Resistance against Witchweed (Striga asiatica L. Kuntze)

Abstract: Sorghum (Sorghum bicolor L. Moench) production in sub-Saharan Africa is seriously constrained by both biotic and abiotic stresses. Among the biotic stresses is witchweed (Striga spp.), a noxious parasitic weed causing major damage in cereal crops, such as sorghum. However, resistance through reduced germination stimulant production or altered germination stimulant composition provides a sustainable and most effective way for managing the parasitic weeds. Laboratory and glasshouse experiments were conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The parasitism of witchweed (Striga spp.) has a significant impact on the head index, leaf biomass, leaf index, root biomass, root index, plant biomass, and root: shoot ratio of sorghum (Sorghum bicolor L. Moench) [16]. Rhinanthus minor has a direct negative influence on host productivity and competitive ability, which helps reconstruct plant communities in grassland [17].…”
Section: Discussionmentioning
confidence: 99%
“…The parasitism of witchweed (Striga spp.) has a significant impact on the head index, leaf biomass, leaf index, root biomass, root index, plant biomass, and root: shoot ratio of sorghum (Sorghum bicolor L. Moench) [16]. Rhinanthus minor has a direct negative influence on host productivity and competitive ability, which helps reconstruct plant communities in grassland [17].…”
Section: Discussionmentioning
confidence: 99%
“…The chlorophyll content is another parameter negatively impacted by Striga infestation in host plants (Gwatidzo et al, 2020;Makani et al, 2020). Previous studies showed also that Striga parasitism causes distress in C production in host plants, which may limit N and Mg assimilation, resulting in low chlorophyll synthesis (Gurney et al, 2002;Mwangangi et al, 2021).…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…Identification of stress resistance/tolerance in crop genotypes is one of the major ways to control crop pests and diseases and reduce the impact of abiotic stresses through crop improvement. For instance, sorghum genotypes tolerant to witchweed in Zimbabwe were identified which could be grown in areas prone to witchweed infestations [91]. The breeding techniques of screening genotypes for stress tolerance/resistance is also being used in identifying maize, wheat and sorghum genotypes with tolerance to heat, drought and combined heat and drought stress conditions [42,52].…”
Section: Increasing the Resilience Of Cereal Production Systems 41 Breeding For Stress Tolerance/resistancementioning
confidence: 99%